TINJAUAN YURIDIS PUTUSAN KOMISI PENGAWAS PERSAINGAN USAHA TENTANG PERSEKONGKOLAN MENENTUKAN PEMENANG TENDER PENGADAAN BARANG DAN JASA BIDANG ALAT KEDOKTERAN, KESEHATAN DAN KB TAHUN ANGGARAN 2011 DI KOTA BATAM (PUTUSAN PERKARA NOMOR 10/KPPU-L/2013) - Vitis Sera; Mardalena Hanifah; Rahmad Hendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
For economic growth and development can not be separated on interference of the Government in the economic activity. The shape of the intervention of the Government include the establishment of Law Number 5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition, which is the purpose of the establishment of the Act is to provide equal opportunities for citizens or businesses to run their businesses, creating a climate of a healthy business, conducive, competitive and improve people's welfare. In the Act there are provisions concerning the activities, one of which is a conspiracy that could lead to monopolistic practices and or unfair business competition. In the study the authors make is about the violation of Article 22 of Law Number 5 of 1999, which in Case Decision Number 10 / KPPU – L / 2013 of conspiracy determine the winner of the tender for Procurement of Goods and Services Sector, Medical Equipment, Health and Family Planning Fiscal Year 2011 in Batam. From the research that the author created, which became the central issue is: How conspiracy in menentuan winning bidder Procurement in Case Commission's Decision No. 10 / KPPU-L / 2013 of conspiracy determine the winner of the tender for Procurement of Goods and Services Sector, Medical Equipment, Health and Family Planning Fiscal year 2011 in the city of Batam. How legal considerations Business Competition Supervisory Commission of the conspiracy in the Commission's Decision on Case No. 10 / KPPU - L / 2013. The method used in this study is if the views of its kind, the study included in this type of normative research, while judging from the nature of this research is descriptive that provide the data as accurately as possible about the fundamental issues that the author adopted with the purpose of obtaining the answers to these problems and to assist in perpetrate the old theories or in order to construct new theories, which intends to provide a clear picture and details about how the implementation of the law, both in theory and in practice to be described as well the principles of law between the regulatory Act number 5 of 1999 in Case Decision number 10 / KPPU-L / 2013. The research results are of Conspiracy on convictions Case Number 10 / KPPU-L / 2013, then the Commission commissioned Preliminary Examination team, Advanced Inspection to conduct an investigation into Case Decision No. 10 / KPPU-L / 2013. Legal considerations of the Commission in Case Decision No. 10 / KPPU-L / 2013, by conducting a series of investigations that are assigned to the Investigation Team, then collected evidence, namely Letters and Documents of the Party, as well as gathering information from witnesses and Reported, so that the results of the examination and tools evidence-tool as consideration of the Commission to decide Case Number 10 / KPPU-L / 2013. Keywords: KPPU-Procurement-Tender